The Grey Partridge (Francolinus Pondicerianus) in the Rajasthan Desert - Sharma, Indra Kumar (Annals of Arid Zone, 2016)
The Grey partridge (Francolinus pondiccrianlls) is a common ground bird of the Rajasthan desert. Its habitat covers a variety of biotopes ranging from sandy scrub to rocky scrub to agricultural farms. It feeds on both seeds and insects and roosts under bushes or thorn fences or on the branches of trees like Prosopis cineraria and Acacia nilotica. The bird drinks water twice every day and sunbathes regularly. The Grey partridge usually moves as a pair, comprising a male and a female, along with their brood of chicks, if any. It breeds from February to April, and from July to October. The mode clutch size is of 6 eggs, and the average brood size is of 6-7 chicks. There are many predatory species feeding on this bird, the principal among which is the Shikra bird (Accipiter badius).